Phosphorus-containing polyphenyl ether resin composition, prepreg containing same and laminated board

By using a phosphorus-containing polyphenylene ether resin composition in a high-speed substrate material, combining double bond-capped polyphenylene ether and a polyphenylene phosphazene compound with a specific structure, the problem of difficulty in meeting dielectric properties, heat resistance and halogen-free flame retardant are solved in the prior art, and excellent flame retardant and dielectric properties are achieved.

CN119798573APending Publication Date: 2025-04-11GUANGDONG SHENGYI SCI TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311296538.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to meet the requirements of high-speed substrate materials for excellent dielectric properties, heat resistance and halogen-free flame retardancy.

Method used

The phosphorus-containing polyphenylene ether resin composition, including double bond-capped polyphenylene ether, polyphenyloxyphosphazene compound with a specific structure as flame retardant and free radical initiator, is used to achieve flame retardant at the UL 94V-0 level and excellent dielectric properties, heat resistance and filler properties by optimizing the component ratio and addition amount.

Benefits of technology

It realizes that the flame retardant at a lower additive amount achieves flame retardant of UL 94V-0 level, while ensuring that the resin composition has excellent dielectric properties, heat resistance and glue filling properties, and is suitable for the process production of multi-layer printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004483116990000031
    Figure BDA0004483116990000031
  • Figure BDA0004483116990000051
    Figure BDA0004483116990000051
  • Figure BDA0004483116990000054
    Figure BDA0004483116990000054
Patent Text Reader

Abstract

The invention provides a phosphorus-containing polyphenyl ether resin composition, a prepreg containing the same and a laminated board, the phosphorus-containing polyphenyl ether resin composition comprises double-bond-terminated polyphenyl ether, a flame retardant and a free radical initiator, and the flame retardant is limited to comprise a polyphenoxy phosphazene compound with a structure as shown in a formula I, in the polyphenoxy phosphazene compound with the structure as shown in the formula I, k: i = 1.5: 0.5, so that the phosphorus-containing polyphenyl ether resin composition also has excellent flame retardance under the condition that the addition amount of the flame retardant is relatively low, can realize UL94V-0-level flame retardance, also has excellent heat resistance, dielectric property and glue filling property, and can be widely applied to the field of flame retardants. And a prepreg, a laminated board and a copper-clad plate which are made of the epoxy resin also have excellent dielectric property, heat resistance and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-clad laminates, and in particular relates to a phosphorus-containing polyphenylene ether resin composition, a prepreg and a laminate containing the same. Background Art

[0002] In recent years, with the continuous development of high performance, high functionality and networking of computers and information communication equipment, in order to transmit and process large-capacity information at high speed, the operating signals tend to be high-frequency, thus putting forward higher requirements on the materials of circuit substrates, especially in those electronic devices using broadband, such as mobile communication devices. Among the existing materials used for printed circuit substrates, epoxy resins with excellent bonding properties are widely used; however, the dielectric constant and dielectric loss tangent of epoxy resin circuit substrates are generally high (dielectric constant is greater than 4, dielectric loss tangent is about 0.02), and the high-frequency characteristics are insufficient, which cannot meet the requirements of high-frequency signals. Therefore, it is necessary to develop resins with excellent dielectric properties, that is, resins with low dielectric constants and dielectric loss tangents to solve the above problems.

[0003] For a long time, technicians in this field have conducted extensive research on thermosetting cyanate esters, bismaleimide resins, hydrocarbon resins, etc. with good dielectric properties; in addition, polyphenylene ether resins have good dielectric properties, heat resistance and other properties, and have also been widely studied by technicians as high-frequency and high-speed materials. However, due to the high melting point and poor fluidity of polyphenylene ether resins, the melt viscosity of the prepreg prepared is large and cannot meet the process requirements of multi-layer printed circuit boards; a common solution is to solve the above problem by reducing the molecular weight of polyphenylene ether resins. Although this method can effectively reduce its melting temperature and improve its fluidity, it also sacrifices the heat resistance of polyphenylene ether resins.

[0004] From the above content, it can be seen that the functionalization of low molecular weight polyphenylene ether is an effective means to solve the problem of reduced heat resistance caused by the reduction of molecular weight of polyphenylene ether. However, further research is needed on how to choose appropriate curing and cross-linking functionalization to give full play to the performance advantages of polyphenylene ether resin. In addition, with the strengthening of social awareness of environmental protection, the environmental protection issues of electronic products are becoming increasingly prominent. How to achieve halogen-free substrate materials has also been the focus of research in this technical field this year. At present, the technical means to achieve halogen-free flame retardancy mainly introduce phosphorus elements for flame retardancy. Common substances include phosphorus-containing epoxy resins, phosphorus-containing phenolic resins, phosphate compounds and polyphosphate compounds, phosphazene compounds, hypophosphite compounds, etc. However, due to the limitations of the characteristics of the above materials themselves, they cannot meet the requirements of heat resistance and dielectric properties in the field of high-speed materials. For example, some materials in phosphorus-containing epoxy resins and phosphorus-containing phenolic resins are Although it can achieve a good flame retardant effect, it has poor performance in dielectric properties and the introduction of too much phosphorus will lead to the deterioration of moisture and heat resistance, which cannot meet the reliability requirements of multi-layer PCBs. When added, phosphinates have poor flame retardant effects when used alone, especially in resin systems with low charring. Generally, polyphosphazene compounds have a relatively low melting point and strong plasticity. A large amount of addition will lead to a significant decrease in heat resistance, such as a decrease in glass transition temperature. Even if a large amount is added, it is difficult to achieve a flame retardant level of V-0. Other phosphate compounds also have similar problems. Overall, how to simultaneously meet the excellent dielectric properties required by high-speed substrate materials while maintaining good heat resistance and halogen-free flame retardancy is one of the key research directions in this field in the future.

[0005] CN11128598A discloses a halogen-free low dielectric resin composition, comprising a polyphenylene ether resin of unsaturated functional groups, a multifunctional vinyl aromatic copolymer and an allyl cyclophosphazene compound. The composition has good physical and chemical properties and dielectric properties, and has good formability and welding heat resistance, but the allyl group reactivity in the allyl cyclophosphazene compound is weak, and has no significant improvement effect on the heat resistance of the resin composition, and even deteriorates the physical and chemical properties of the obtained resin composition. Although a large amount of free radical initiators can be added to obtain ideal reactivity, adding a large amount of free radical initiators will have an adverse effect on the dielectric properties of the resin composition, so it is impossible to meet the needs of high-speed materials in high-level applications.

[0006] CN102977551A discloses a halogen-free resin composition, which includes reactive allylphenoxy cyclotriphosphazene or vinylphenoxy cyclotriphosphazene, a thermosetting resin, a crosslinking curing agent, a crosslinking curing accelerator and a filler. The resin composition can improve the dielectric properties of the system while meeting the halogen-free flame retardant requirements, but the added halogen-free flame retardant does not have a preferred restriction on the ratio of phenoxy and vinylphenoxy in the flame retardant structure, so the improvement effect on the dielectric properties and flame retardant properties of the resin composition is not significant.

[0007] Therefore, it is expected to develop a phosphorus-containing polyphenylene ether resin composition having excellent dielectric properties, heat resistance, flame retardancy and physical and chemical properties. Summary of the invention

[0008] In view of the deficiencies of the prior art, the object of the present invention is to provide a phosphorus-containing polyphenylene ether resin composition, a prepreg and a laminate comprising the same, wherein the phosphorus-containing polyphenylene ether resin composition has excellent flame retardancy, dielectric properties and heat resistance, as well as excellent flow filling performance.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a phosphorus-containing polyphenylene ether resin composition, the phosphorus-containing polyphenylene ether resin composition comprising a double-bond terminated polyphenylene ether, a flame retardant and a free radical initiator;

[0011] The flame retardant includes a polyphenoxyphosphazene compound having a structure shown in Formula I;

[0012]

[0013] Among them, n=3, k:i=1.5:0.5.

[0014] The phosphorus-containing polyphenylene ether resin composition provided by the present invention comprises a double-bond terminated polyphenylene ether, a flame retardant and a free radical initiator. The flame retardant is limited to a polyphenoxyphosphazene compound having a structure shown in Formula I. In the polyphenoxyphosphazene compound having a structure shown in Formula I, k:i=1.5:0.5 is limited, so that the prepared phosphorus-containing polyphenylene ether resin composition has excellent dielectric properties, heat resistance and filling ability, and at the same time, the flame retardant can achieve UL 94V-0 level flame retardancy when added in a relatively low amount. If the ratio of k:i is higher than 1.5:0.5, the heat resistance of the resin composition will be affected, and if the ratio of k:i is lower than 1.5:0.5, the filling capacity of the resin composition will decrease. Only when k:i=1.5:0.5 can a phosphorus-containing polyphenylene ether resin composition having excellent dielectric properties, heat resistance, flame retardant properties and filling capacity be obtained, and thus the prepreg and copper clad laminate made of the phosphorus-containing polyphenylene ether resin composition also have excellent dielectric properties, heat resistance and flame retardant properties, and reach the flame retardancy of UL 94V-0 level.

[0015] It should be noted that the reason why k:i in the polyphenoxyphosphazene compound of the structure shown in Formula I is 1.5:0.5 is that when preparing the compound of the above structure, it cannot be guaranteed that the phenoxy group and the vinylphenoxy group can be grafted onto each P atom in a ratio of 3:1. After the product is obtained and tested, the ratio of the number of phenoxy groups to vinylphenoxy groups is 1.5:0.5, which is an average value.

[0016] Preferably, based on 100 parts by weight of the double-bond terminated polyphenylene ether in the phosphorus-containing polyphenylene ether resin composition, the content of the polyphenoxyphosphazene compound is 15 to 40 parts by weight, for example, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight or 35 parts by weight, etc., preferably 20 to 25 parts by weight.

[0017] As a preferred technical solution of the present invention, the polyphenoxyphosphazene compound having the structure shown in Formula I is easily soluble in solvents such as ketones and aromatic hydrocarbons, and has good compatibility with double-bond terminated polyphenylene ether. In order to ensure that the phosphorus-containing polyphenylene ether resin composition has excellent flame retardancy and low smoke release after curing, it is necessary to limit the addition amount of the polyphenoxyphosphazene compound to 15 to 40 parts by weight. On the one hand, if the addition amount is less than 15 parts by weight, the phosphorus content in the resin composition will be insufficient, and the flame retardancy of 94UL V-0 level will not be achieved; on the other hand, if the addition amount exceeds 40 parts by weight, although the flame retardancy of the resin composition can be ensured to be excellent, the dielectric loss of the resin composition will increase, the rigidity will decrease, and the water absorption will increase significantly.

[0018] Preferably, the double bond group in the double-bond terminated polyphenylene ether includes any one of methyl methacrylate, vinyl benzyl, vinyl, styrene or allyl, or a combination of at least two of them.

[0019] Preferably, the double bond terminated polyphenylene ether is vinylated polyphenylene ether.

[0020] Preferably, the vinyl polyphenylene ether has a structure as shown in the following formula II:

[0021]

[0022] In Formula II, a and b are each independently selected from integers between 1 and 30 (e.g., 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26 or 28, etc.), and Z has the structure shown in Formula III or Formula IV, The structure is shown in formula V, It is the structure shown in formula VI;

[0023]

[0024] In formula IV, A is selected from arylene, or any one of C1-C10 (e.g., C2, C4, C6 or C8, etc.) alkylene, R1-R3 are each independently selected from H or any one of C1-C10 (e.g., C2, C4, C6 or C8, etc.) alkyl, m is selected from an integer between 0 and 10 (e.g., 2, 4, 6 or 8, etc.), and * represents a connection site;

[0025]

[0026] In formula V, R4 and R6 are each independently selected from any one of H, halogen, C1-C8 (e.g., C2, C3, C4, C5C6 or C7, etc.) alkyl or phenyl; R5 and R7 are each independently selected from any one of halogen, C1-C8 (e.g., C2, C3, C4, C5C6 or C7, etc.) alkyl or phenyl, and * represents a connection site;

[0027]

[0028] In Formula VI, R8~R 15 Each is independently selected from H, halogen, C1-C8 (e.g., C2, C3, C4, C5C6 or C7, etc.) alkyl or phenyl, and B is selected from C1-C20 alkylene, *-o-*, Any one of R 16 is selected from H or C1-C10 (eg, C2, C3, C4, C5C6 or C7, etc.) alkyl, * represents the connection site, and m is 0 or 1.

[0029] Preferably, the number average molecular weight of the double-bond terminated polyphenylene ether is 1500-6000 g / mol, for example, 2000 g / mol, 3000 g / mol, 4000 g / mol or 5000 g / mol.

[0030] It should be noted that the above number average molecular weight is measured by gel permeation chromatography based on polystyrene calibration in accordance with GB / T 21863-2008.

[0031] In the technical field of copper clad laminates, fluidity is one of the key indicators of formulation processability, so the present invention preferably uses a double-bond terminated polyphenylene ether with a number average molecular weight of 1500 to 6000 g / mol. On the one hand, if its number average molecular weight is greater than 6000 g / mol, its viscosity is too high, which will cause the fluidity of the phosphorus-containing polyphenylene ether resin composition to deteriorate seriously and make it difficult to process smoothly; on the other hand, if the number average molecular weight of the double-bond group terminated polyphenylene ether is lower than 1500 g / mol, its own dielectric properties, rigidity, etc. will also deteriorate, and the comprehensive performance of the laminated board prepared subsequently cannot be guaranteed. At the same time, it will also bring about the problem of excessive gel flow, which will also make the production and processing too difficult.

[0032] Preferably, the free radical initiator comprises a peroxide initiator.

[0033] Preferably, the free radical initiator has a t 1 / 2 Not higher than 300°C, for example, 290°C, 280°C, 270°C, 260°C, 250°C, 240°C, 230°C, 220°C, 210°C, 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 110°C or 100°C, etc.

[0034] Preferably, the free radical initiator comprises tert-butyl peroxyacetate, 2,2-bis(tert-butyl peroxy)octane, tert-butyl peroxyisopropyl carbonate, 1,1-bis(tert-butyl peroxy)cyclohexanone, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexanone, tert-butyl peroxyoctanoate, tert-butyl peroxyisobutyrate, disuccinic acid peroxide, di-toluoyl peroxide, ditoluoyl peroxide, diacetyl peroxide, isopropyl peroxyoctanoate, didecanoyl peroxide, dioct ... Dialkanoyl peroxide, bis(3,5,5-trimethylacetyl peroxide), tert-butyl peroxypivalate, tert-hexyl peroxypivalate, tert-butyl peroxyneohexanoate, tert-hexyl peroxyneohexanoate, bis(3-methyl-3-methoxybutyl peroxyhydrocarbonate), tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, isopropyl peroxyneohexanoate, bismethoxyisopropyl peroxyhydrocarbonate, ditetradecyl peroxyhydrocarbonate, diallyl peroxyhydrocarbonate, isopropyl peroxyneodecanoate, dimethoxyisopropyl peroxyhydrocarbonate n-propyl peroxydicarbonate, bis(2-hydroxyethylhexyl peroxydicarbonate), bis(2-ethylhexyl peroxydicarbonate), di-n-butyl peroxydicarbonate, diisobutyl peroxydicarbonate, diisobutylene peroxide, diisopropyl peroxydicarbonate, acetylcyclohexylsulfonyl peroxide, tert-butyl hydroperoxide, tetramethylbutane peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne, di-tert-butyl peroxide, a,a-bis(tert-butylperoxy-m-isopropylphenyl), 2,5-dimethyl any one of tert-butylperoxy)hexane, tert-butyl isopropyl peroxide, tert-butyl peroxyallyl bicarbonate, diisopropyl peroxide, tert-butyl peroxybenzoate, di-tert-butyl peroxyisophthalate, n-butyl-4,4-bis(tert-butylperoxy)valerate, tert-butyl peroxy(3,5,5-trimethylacetate), tert-butyl peroxylaurate, 2,5-dimethyl-2,5-di(dibenzoylperoxy)hexane or 2,2-bis(tert-butylperoxy)butane, or a combination of at least two thereof.

[0035] As a preferred technical solution of the present invention, the introduction of the above-mentioned free radical initiator helps to improve the process efficiency and curing degree of the resin composition. Although the curing reaction of the phosphorus-containing polyphenylene ether resin composition can be initiated by temperature, the high temperature used in the lamination process cannot meet the required degree of curing, and the production process is very difficult. The introduction of the free radical initiator can effectively improve the process efficiency and can produce a laminate with a suitable degree of curing.

[0036] Preferably, based on 100 parts by weight of the total content of the resin components in the phosphorus-containing polyphenylene ether resin composition, the content of the free radical initiator is 0.1 to 3 parts by weight, for example, 0.2 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight or 2.5 parts by weight.

[0037] As a preferred technical solution of the present invention, it is necessary to limit the amount of free radical initiator to 0.1 to 3 parts by weight. On the one hand, if the amount of free radical initiator added is too little, it will lead to a low degree of curing of the resin composition. On the other hand, if the amount of free radical initiator added is too high, it will affect the dielectric properties of the resin composition.

[0038] Preferably, the phosphorus-containing polyphenylene ether resin composition further comprises a crosslinking agent.

[0039] Preferably, the crosslinking agent includes any one or a combination of at least two of a styrene-butadiene copolymer containing a double bond, triallyl isocyanurate, triallyl cyanurate, a multifunctional acrylate compound, a bismaleimide resin, divinylbenzene, a polybutadiene-styrene-butadiene-divinylbenzene copolymer or a multifunctional vinyl aromatic copolymer.

[0040] Preferably, based on the total weight of double bonds in the cross-linking agent as 100%, the content of vinyl in the cross-linking agent is greater than 40%, for example, 45%, 50%, 55%, 60%, 65%, 70%, 80% or 90%, etc., more preferably greater than 70%.

[0041] Preferably, based on 100 parts by weight of the double-bond terminated polyphenylene ether in the phosphorus-containing polyphenylene ether resin composition, the content of the cross-linking agent is 10 to 80 parts by weight, for example, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 34 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight or 75 parts by weight, etc.

[0042] As a preferred technical solution of the present invention, the above-mentioned cross-linking agent is selected and added to the phosphorus-containing polyphenylene ether resin composition, and more double bonds are introduced to participate in the reaction, which helps to further improve the cross-linking density of the resin composition and form a more heat-resistant and rigid network structure; at the same time, it is necessary to limit the addition amount of the cross-linking agent to 10 to 80 parts by weight. If the addition amount is too little, the degree of cross-linking will be insufficient and the purpose of reinforcement will not be achieved. If the addition amount is too much, the dielectric loss of the system will be deteriorated due to the increase in polarity.

[0043] Preferably, the phosphorus-containing polyphenylene ether resin composition further comprises a silane coupling agent.

[0044] Preferably, based on 100 parts by weight of the total content of the double-bond terminated polyphenylene ether and the crosslinking agent in the phosphorus-containing polyphenylene ether resin composition, the amount of the silane coupling agent is 0.1 to 2 parts by weight, for example, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight or 1.8 parts by weight, etc.

[0045] As a preferred technical solution of the present invention, the addition of silane coupling agent helps to increase the interfacial tension, improve the bonding force between the resin matrix and the filler, and help to form an organic whole.

[0046] Preferably, the phosphorus-containing polyphenylene ether resin composition further comprises a filler.

[0047] Preferably, based on 100 parts by weight of the total content of the double-bond terminated polyphenylene ether and the crosslinking agent in the phosphorus-containing polyphenylene ether resin composition, the amount of the filler is 10 to 80 parts by weight, for example, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight or 70 parts by weight, etc., more preferably 30 to 60 parts by weight.

[0048] Preferably, the filler includes any one of silicon dioxide, glass powder, aluminum nitride, boron nitride, silicon carbide, aluminum hydroxide, titanium dioxide, strontium titanate, barium titanate, aluminum oxide, barium sulfate, talc, calcium silicate, calcium carbonate or mica, or a combination of at least two thereof.

[0049] Preferably, the silica comprises crystalline silica or fused silica.

[0050] Preferably, the silicon dioxide comprises spherical solid silicon dioxide and / or spherical hollow silicon dioxide.

[0051] Preferably, the phosphorus-containing polyphenylene ether resin composition further comprises any one of an antioxidant, a stabilizer, an antistatic agent, an ultraviolet absorber, a colorant or a lubricant, or a combination of at least two thereof.

[0052] In the present invention, there is no particular limitation on the type of solvent used in the phosphorus-containing polyphenylene ether resin composition and the solvent to form the glue solution, and there is no particular limitation on the amount of the solvent added. The technical personnel in this field can select the solvent according to their own needs so that the glue solution of the phosphorus-containing polyphenylene ether resin composition can reach a suitable viscosity for use.

[0053] Exemplarily, the solvent can be selected from any one of methanol, ethanol, butanol, ethyl cellosolve, butyl cellosolve, ethylene glycol methyl ether, carbitol, butyl carbitol, acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene, xylene, ethyl acetate, ethoxyethyl acetate, N,N-dimethylformamide or N,N-dimethylacetamide, or a combination of at least two thereof.

[0054] In a second aspect, the present invention provides a prepreg, comprising a reinforcing material, and the phosphorus-containing polyphenylene ether resin composition as described in the first aspect attached to the reinforcing material after impregnation and drying.

[0055] Preferably, the reinforcing material includes any one of organic fiber cloth, inorganic fiber cloth or non-woven fabric.

[0056] Preferably, the inorganic fiber cloth is E-fiberglass cloth, D-fiberglass cloth, S-fiberglass cloth, T-fiberglass cloth, NE-fiberglass cloth or quartz cloth.

[0057] Preferably, the thickness of the reinforcing material is 0.01-0.2 mm, for example, 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.12 mm, 0.14 mm, 0.16 mm or 0.18 mm.

[0058] As a preferred technical solution of the present invention, the reinforcing material is preferably a reinforcing material that has undergone fiber opening treatment and silane coupling agent surface treatment, and the silane coupling agent used in the silane coupling agent surface treatment includes any one of epoxy silane coupling agent, amino silane coupling agent or vinyl silane coupling agent, or a combination of at least two of them.

[0059] In a third aspect, the present invention provides a laminate, comprising one or at least two laminated prepregs as described in the second aspect.

[0060] In a fourth aspect, the present invention provides a copper clad laminate comprising one or at least two laminated prepregs as described in the second aspect, and copper foil covering one side or both sides of the prepreg or the laminated prepregs.

[0061] In a fifth aspect, the present invention provides a printed circuit board, wherein the printed circuit board comprises the prepreg as described in the second aspect, the laminate as described in the third aspect, or the copper clad board as described in the fourth aspect.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The phosphorus-containing polyphenylene ether resin composition provided by the present invention comprises a combination of a double-bond terminated polyphenylene ether, a flame retardant and a free radical initiator, wherein the flame retardant comprises a polyphenoxyphosphazene compound having a structure shown in Formula I, and in the polyphenoxyphosphazene compound having a structure shown in Formula I, k:i=1.5:0.5 is defined so that the flame retardant can achieve UL 94V-0 level flame retardancy with a relatively low addition amount, and at the same time ensure that the obtained phosphorus-containing polyphenylene sulfide resin composition has excellent heat resistance, flame retardancy, dielectric properties and glue filling properties, and thus the prepreg, laminate and copper-clad laminate made thereof all have excellent dielectric properties and heat resistance, and can achieve UL 94-V0 level flame retardancy under halogen-free conditions. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] The information of some raw materials involved in the specific implementation of the present invention is shown in Table 1:

[0066] Table 1

[0067]

[0068]

[0069] Preparation Example 1

[0070] Preparation of SY-0: 400 mL of dry tetrahydrofuran, 10.00 g (0.0288 mol) of hexachlorocyclotriphosphazene, 18.9 g (0.1545 mol) of vinylphenol, 6.3 g (0.0515 mol) of phenol and 45.50 g (0.33 mol) of potassium carbonate were added to a 500 mL three-necked flask in sequence, and the mixture was refluxed for 48 h under stirring under argon protection. After the reaction was completed, the mixture was evaporated under reduced pressure at 40 ° C on a rotary evaporator. About 1 / 2 volume of tetrahydrofuran, the remaining solid and liquid are poured into 800 mL of distilled water and stirred for precipitation. After stirring for about 5 minutes, it is allowed to stand, filtered, and the solid is repeatedly washed with distilled water. Finally, the solid is placed in a vacuum drying oven at 50 ° C and dried for 24 hours to obtain 23.87 g of white powdery solid with a crude yield of more than 96%. It is recrystallized with ethyl acetate (about 1.5 mL of ethyl acetate is required for 0.1 g of solid) to obtain white needle-shaped crystals, which is the flame retardant SY-0.

[0071] Comparative Preparation Example 1

[0072] Preparation of SY-1: 400 mL of dry tetrahydrofuran, 10.00 g (0.0288 mol) of hexachlorocyclotriphosphazene, 12.6 g (0.103 mol) of vinylphenol, 12.6 g (0.103 mol) of phenol and 45.50 g (0.33 mol) of potassium carbonate were added to a 500 mL three-necked flask in sequence, and the mixture was refluxed for 48 h under stirring under argon protection. After the reaction was completed, about 1 / 2 volume of tetrahydrofuran was evaporated under reduced pressure at 40° C. on a rotary evaporator, and the remaining solid and liquid were poured into 800 mL of distilled water and stirred for precipitation. After stirring for about 5 min, the mixture was allowed to stand, filtered, and the solid was repeatedly washed with distilled water. Finally, the solid was placed in a vacuum drying oven at 50° C. and dried for 24 h to obtain 23.87 g of a white powdery solid with a crude yield of more than 96%. The solid was recrystallized from ethyl acetate (about 1.5 mL of ethyl acetate was required for 0.1 g of the solid) to obtain white needle-shaped crystals of SY-1.

[0073] Comparative Example Preparation Example 2

[0074] Preparation of SY-2: 400 mL of dry tetrahydrofuran, 10.00 g (0.0288 mol) of hexachlorocyclotriphosphazene, 6.3 g (0.0515 mol) of vinylphenol, 18.9 g (0.1545 mol) of phenol and 45.50 g (0.33 mol) of potassium carbonate were added to a 500 mL three-necked flask in sequence, and the mixture was refluxed for 48 h under stirring under argon protection. After the reaction was completed, about 1 / 2 volume of tetrahydrofuran was evaporated under reduced pressure at 40° C. on a rotary evaporator, and the remaining solid and liquid were poured into 800 mL of distilled water and stirred for precipitation. After stirring for about 5 min, the mixture was allowed to stand, filtered, and the solid was repeatedly washed with distilled water. Finally, the solid was placed in a vacuum drying oven at 50° C. and dried for 24 h to obtain 23.87 g of a white powdery solid with a crude yield of more than 96%. The solid was recrystallized from ethyl acetate (about 1.5 mL of ethyl acetate was required for 0.1 g of the solid) to obtain white needle-shaped crystals of SY-2.

[0075] Comparative Example Preparation Example 3

[0076] Preparation of SY-3: 400 mL of dry tetrahydrofuran, 10.00 g (0.0288 mol) of hexachlorocyclotriphosphazene, 21 g (0.172 mol) of vinylphenol, 4.2 g (0.034 mol) of phenol and 45.50 g (0.33 mol) of potassium carbonate were added to a 500 mL three-necked flask in sequence, and the mixture was refluxed for 48 h under stirring under argon protection. After the reaction was completed, about 1 / 2 volume of tetrahydrofuran was evaporated under reduced pressure at 40° C. on a rotary evaporator, and the remaining solid and liquid were poured into 800 mL of distilled water and stirred for precipitation. After stirring for about 5 min, the mixture was allowed to stand, filtered, and the solid was repeatedly washed with distilled water. Finally, the solid was placed in a vacuum drying oven at 50° C. and dried for 24 h to obtain 23.87 g of a white powdery solid with a crude yield of more than 96%. The solid was recrystallized from ethyl acetate (about 1.5 mL of ethyl acetate was required for 0.1 g of the solid) to obtain white needle-shaped crystals of SY-3.

[0077] Comparative Example Preparation Example 4

[0078] Preparation of SY-4: 400 mL of dry tetrahydrofuran, 10.00 g (0.0288 mol) of hexachlorocyclotriphosphazene, 4.2 g (0.034 mol) of vinylphenol, 21 g (0.172 mol) of phenol and 45.50 g (0.33 mol) of potassium carbonate were added to a 500 mL three-necked flask in sequence, and the mixture was refluxed under stirring for 48 h under argon protection. After the reaction was completed, about 1 / 2 volume of tetrahydrofuran was evaporated under reduced pressure at 40° C. on a rotary evaporator, and the remaining solid and liquid were poured into 800 mL of distilled water and stirred for precipitation. After stirring for about 5 min, the mixture was allowed to stand, filtered, and the solid was repeatedly washed with distilled water. Finally, the solid was placed in a vacuum drying oven at 50° C. and dried for 24 h to obtain 23.87 g of a white powdery solid with a crude yield of more than 96%. The solid was recrystallized from ethyl acetate (about 1.5 mL of ethyl acetate was required for 0.1 g of the solid) to obtain white needle-shaped crystals of SY-4.

[0079] Examples 1 to 5 and Comparative Examples 1 to 7

[0080] A phosphorus-containing polyphenylene ether resin composition, the components of which are shown in Table 2, and the amounts are all in parts by weight:

[0081] Table 2

[0082]

[0083] The preparation method of the phosphorus-containing polyphenylene ether resin composition comprises: uniformly mixing the components in Table 2 to obtain the phosphorus-containing polyphenylene ether resin composition.

[0084] Example 6

[0085] A phosphorus-containing polyphenylene ether resin composition, which is different from Example 3 only in that the added amount of FP-700TP is 27 parts by weight, and the other components, amounts and preparation methods are the same as those of Example 3.

[0086] Example 7

[0087] A phosphorus-containing polyphenylene ether resin composition, which is different from Example 3 only in that the added amount of FP-700TP is 9 parts by weight, and the other components, amounts and preparation methods are the same as those of Example 3.

[0088] Application Examples 1 to 7 and Comparative Application Examples 1 to 7

[0089] A copper clad laminate, the preparation method of which comprises the following steps:

[0090] (1) The phosphorus-containing polyphenylene ether resin compositions obtained in Examples 1 to 7 and Comparative Examples 1 to 7 were respectively mixed with butanone in a mass ratio of 65:35 to obtain a glue solution;

[0091] (2) The adhesive prepared in step (1) is impregnated into the reinforcing material glass fiber cloth 1078, and heated and dried at 145° C. for 2.5 min to completely evaporate the solvent to obtain a prepreg. The above prepregs are overlapped, and finally copper foil is attached to both sides of the overlapped prepregs, and hot pressed at 210° C. and 2.1 MPa for 120 min to obtain the copper clad laminate.

[0092] Performance Testing:

[0093] The following performance tests were performed on the copper clad laminates obtained from application examples 1 to 7 and comparative application examples 1 to 7:

[0094] (1) Glass transition temperature (Tg): tested using IPC-TM-650 2.4.24.4 standard method;

[0095] (2) Flame retardant level: tested according to the UL9450W (20mm) vertical combustion test method, the test results are V-0, V-1 and V-2 respectively;

[0096] (3) Dielectric constant (10 GHz): tested using IPC-TM-650 2.5.5.5 standard method, frequency 10 GHz;

[0097] (4) Dielectric loss tangent (10 GHz): tested using IPC-TM-650 2.5.5.5 standard method, frequency 10 GHz;

[0098] (5) Copper foil peel strength (PS) test: IPC-TM-650 2.4.8.1 standard method is used for testing; the testing instrument is a peel strength tester;

[0099] (6) Solder immersion resistance: After being kept in a pressure cooking treatment device at 121°C and 105 kPa for 2 hours, the sample (100 mm × 100 mm substrate) was immersed in a solder bath heated to 260°C for 20 seconds. The sample was observed with the naked eye for delamination, white spots or wrinkles. The symbol ○ in the table indicates no change, △ indicates white spots, and × indicates delamination.

[0100] The following performance tests were performed on the prepregs prepared in Examples 1 to 7 and Comparative Examples 1 to 7:

[0101] (1) Flowability: Tested using IPC-TM-650 2.3.17 standard method at a temperature of 171°C.

[0102] The test was carried out according to the above test scheme, and the test results are shown in Table 3 and Table 4:

[0103] Table 3

[0104]

[0105] Table 4

[0106]

[0107] According to the data in Table 3 and Table 4, we can see that:

[0108] Compared with Example 3, Comparative Examples 1 to 7 cannot have excellent heat resistance, flame retardancy and dielectric properties; wherein, no flame retardant is added in Comparative Example 1, and the flame retardancy level is only V-1, which does not meet the flame retardancy requirements; in Comparative Example 2, non-reactive flame retardant SPB-100 is used, although the flame retardancy of the material is improved, but the heat resistance of the material is reduced, and the dielectric loss tangent of the material is also adversely affected; in Comparative Example 3, SPV-100 is used as a flame retardant, but because of its insufficient reactivity as a flame retardant, the Tg of the material is slightly improved, and the dielectric loss tangent is not improved; and in Comparative Examples 4 to 7, a flame retardant with a structure similar to FP-700TP is used, but because the ratio of phenoxy and vinylphenoxy in the flame retardant is not within the range specified by the present invention, although the Tg of the material is significantly improved, the dielectric properties of the material will be deteriorated, and the flowability will be poor, thereby causing the filling property to deteriorate;

[0109] Compared with Example 3, Example 1 only contains polyphenylene ether, flame retardant FP-700TP and free radical initiator. Although the material can achieve V-0 level flame retardancy, its heat resistance and fluidity are lower than those of Example 3. Examples 4 and 5 change the type and amount of the cross-linking agent, so that the fluidity of the material is increased while the solder resistance and peel strength are reduced. In Example 6, the weight of the flame retardant FP-700TP exceeds the preferred range of the present invention, so the fluidity is poor and the flow filling capacity is insufficient. In Example 7, the amount of the flame retardant FP-700TP added is too small, which is insufficient to achieve a sufficient flame retardant effect.

[0110] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a phosphorus-containing polyphenylene ether resin composition, and a prepreg and a laminate containing the same, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A phosphorus-containing polyphenylene ether resin composition, characterized in that: The phosphorus-containing polyphenylene ether resin composition comprises a double-bond terminated polyphenylene ether, a flame retardant and a free radical initiator; The flame retardant includes a polyphenoxyphosphazene compound having a structure shown in Formula I; Among them, n=3, k:i=1.5:0.

5.

2. The phosphorus-containing polyphenylene ether resin composition according to claim 1, characterized in that: Based on 100 parts by weight of the double-bond terminated polyphenylene ether in the phosphorus-containing polyphenylene ether resin composition, the content of the polyphenoxyphosphazene compound is 15 to 40 parts by weight, preferably 20 to 25 parts by weight; Preferably, the double bond group in the double bond terminated polyphenylene ether includes any one or a combination of at least two of methyl methacrylate, vinyl benzyl, vinyl, styrene or allyl; Preferably, the double-bond terminated polyphenylene ether is vinylated polyphenylene ether; Preferably, the vinyl polyphenylene ether has a structure as shown in the following formula II: In Formula II, a and b are each independently selected from integers between 1 and 30, and Z has a structure shown in Formula III or Formula IV, The structure is shown in formula V, It is the structure shown in formula VI; In formula IV, A is selected from arylene, or any one of C1-C10 alkylene, R1-R3 are each independently selected from H or any one of C1-C10 alkyl, m is selected from an integer between 0 and 10, and * represents a connection site; In Formula V, R4 and R6 are each independently selected from any one of H, halogen, C1-C8 alkyl or phenyl, R5 and R7 are each independently selected from any one of halogen, C1-C8 alkyl or phenyl, and * represents a connection site; In Formula VI, R8~R 15 Each is independently selected from any one of H, halogen, C1-C8 alkyl or phenyl, and B is selected from C1-C20 alkylene, *-O-*, Any one of R 16 is selected from H or C1-C10 alkyl, * represents the connection site, and m is selected from 0 or 1; Preferably, the number average molecular weight of the double-bond terminated polyphenylene ether is 1500 to 6000 g / mol.

3. The phosphorus-containing polyphenylene ether resin composition according to claim 1 or 2, characterized in that: The free radical initiator includes a peroxide initiator; Preferably, the free radical initiator has a t 1 / 2 Not higher than 300℃; Preferably, the free radical initiator comprises tert-butyl peroxyacetate, 2,2-bis(tert-butyl peroxy)octane, tert-butyl peroxyisopropyl carbonate, 1,1-bis(tert-butyl peroxy)cyclohexanone, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexanone, tert-butyl peroxyoctanoate, tert-butyl peroxyisobutyrate, disuccinic acid peroxide, di-toluoyl peroxide, ditoluoyl peroxide, diacetyl peroxide, isopropyl peroxyoctanoate, didecanoyl peroxide, dioct ... Dialkanoyl peroxide, bis(3,5,5-trimethylacetyl peroxide), tert-butyl peroxypivalate, tert-hexyl peroxypivalate, tert-butyl peroxyneohexanoate, tert-hexyl peroxyneohexanoate, bis(3-methyl-3-methoxybutyl peroxyhydrocarbonate), tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, isopropyl peroxyneohexanoate, bismethoxyisopropyl peroxyhydrocarbonate, ditetradecyl peroxyhydrocarbonate, diallyl peroxyhydrocarbonate, isopropyl peroxyneodecanoate, Di-n-propyl peroxydicarbonate, bis(2-hydroxyethylhexyl peroxydicarbonate), bis(2-ethylhexyl peroxydicarbonate), di-n-butyl peroxydicarbonate, diisobutyl peroxydicarbonate, diisobutylene peroxide, diisopropyl peroxydicarbonate, acetylcyclohexylsulfonyl peroxide, tert-butyl hydroperoxide, tetramethylbutane peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne, di-tert-butyl peroxide, a,a-bis(tert-butylperoxy-m-isopropylphenyl), 2,5-di Any one of methyl-2,5-bis(tert-butylperoxy)hexane, tert-butyl isopropyl peroxide, tert-butyl peroxyallyl bicarbonate, diisopropyl peroxide, tert-butyl peroxybenzoate, di-tert-butyl peroxyisophthalate, n-butyl-4,4-bis(tert-butylperoxy)valerate, tert-butyl peroxy(3,5,5-trimethylacetate), tert-butyl peroxylaurate, 2,5-dimethyl-2,5-di(dibenzoylperoxy)hexane or 2,2-bis(tert-butylperoxy)butane, or a combination of at least two thereof; Preferably, based on 100 parts by weight of the total content of the double-bond terminated polyphenylene ether in the phosphorus-containing polyphenylene ether resin composition, the content of the free radical initiator is 0.1 to 3 parts by weight.

4. The phosphorus-containing polyphenylene ether resin composition according to any one of claims 1 to 4, characterized in that: The phosphorus-containing polyphenylene ether resin composition also includes a crosslinking agent; Preferably, the crosslinking agent comprises any one or a combination of at least two of a styrene-butadiene copolymer containing a double bond, triallyl isocyanurate, triallyl cyanurate, a multifunctional acrylate compound, a bismaleimide resin, divinylbenzene, a polybutadiene-styrene-butadiene-divinylbenzene copolymer or a multifunctional vinyl aromatic copolymer; Preferably, based on the total weight of double bonds in the cross-linking agent as 100%, the content of vinyl in the cross-linking agent is greater than 40%, more preferably greater than 70%; Preferably, based on 100 parts by weight of the double-bond terminated polyphenylene ether in the phosphorus-containing polyphenylene ether resin composition, the content of the crosslinking agent is 10 to 80 parts by weight.

5. The phosphorus-containing polyphenylene ether resin composition according to any one of claims 1 to 4, characterized in that: The phosphorus-containing polyphenylene ether resin composition also includes a silane coupling agent; Preferably, based on 100 parts by weight of the total content of the double-bond terminated polyphenylene ether and the crosslinking agent in the phosphorus-containing polyphenylene ether resin composition, the content of the silane coupling agent is 0.1 to 2 parts by weight.

6. The phosphorus-containing polyphenylene ether resin composition according to any one of claims 1 to 5, characterized in that: The phosphorus-containing polyphenylene ether resin composition further includes a filler; Preferably, based on 100 parts by weight of the total content of the double-bond terminated polyphenylene ether and the crosslinking agent in the phosphorus-containing polyphenylene ether resin composition, the content of the filler is 10 to 80 parts by weight, more preferably 30 to 60 parts by weight; Preferably, the filler includes any one or a combination of at least two of silicon dioxide, glass powder, aluminum nitride, boron nitride, silicon carbide, aluminum hydroxide, titanium dioxide, strontium titanate, barium titanate, aluminum oxide, barium sulfate, talc, calcium silicate, calcium carbonate or mica; Preferably, the silicon dioxide comprises crystalline silicon dioxide or fused silicon dioxide; Preferably, the silicon dioxide comprises spherical solid silicon dioxide and / or spherical hollow silicon dioxide; Preferably, the phosphorus-containing polyphenylene ether resin composition further comprises any one of an antioxidant, a stabilizer, an antistatic agent, an ultraviolet absorber, a colorant or a lubricant, or a combination of at least two thereof.

7. A prepreg, characterized in that: The prepreg comprises a reinforcing material, and the phosphorus-containing polyphenylene ether resin composition according to any one of claims 1 to 6 attached to the reinforcing material after impregnation and drying; Preferably, the thickness of the reinforcing material is 0.01-0.2 mm.

8. A laminated board, characterized in that: The laminate comprises one or at least two prepregs according to claim 7 stacked together.

9. A copper clad laminate, characterized in that: The copper clad laminate comprises one or at least two laminated prepregs as claimed in claim 7, and copper foil covering one side or both sides of the prepreg or the laminated prepregs.

10. A printed circuit board, characterized in that: The printed circuit board comprises the prepreg according to claim 7 or the laminate according to claim 8 or the copper clad laminate according to claim 9.

Citation Information

Patent Citations

  • Halogen-free resin composition and method for preparing copper-clad plate from the halogen-free resin composition

    CN102977551A